The Electricity Consumption, Real Income, Trade Openness and FDI: The Empirical Evidence from Turkey - Acaravcı, Ali; Erdogan, Sinan; Akalın, Guray (International Journal of Energy Economics and Policy, 2015)
This study aims to explore both the long-run and causal relationships between electricity consumption per capita, real GDP per capita, trade openness and foreign direct investment inflows per capita in Turkey during the time period 1974–2013. The study employs the ARDL model and the Augmented Granger causality model. The bounds F–test for cointegration test yields evidence of a long-run relationship between variables. The overall results from the three error-correction based Granger causality models show that there is an evidence of unidirectional short-run, long-run and strong causalities running from the electricity consumption per capita to real GDP per capita. However, there is no causal evidence from the real GDP per capita to electricity consumption per capita. This result also support that, “Growth hypothesis” is confirmed in Turkey. As a policy implication, the energy growth policies regarding electricity consumption should be adopted in such a way that the development of this sector stimulates economic growth. Keywords: Electricity consumption; Economic growth; Causality JEL Classifications: C32; C52; Q43